Correction: A hypoxia-specific and mitochondria-targeted anticancer theranostic agent with high selectivity for cancer cells. Issue 26 (26th June 2018) - Hu, Mingxing; Yang, Chao; Luo, Yi; Chen, Fan; Yang, Fangfang; Yang, Shuping; Chen, Hao; Cheng, Zhiqiang; Li, Kun; Xie, Yongmei
Abstract : Correction for 'A hypoxia-specific and mitochondria-targeted anticancer theranostic agent with high selectivity for cancer cells' by Mingxing Hu et al., J. Mater. Chem. B, 2018, 6, 2413–2416.